The Very Fairy Princess : a Spooky, Sparkly Halloween - Andrews, Julie; Hamilton, Emma Walton; Davenier, Christine (New York, 2015)
"Gerry comes up with a creative Halloween costume, but when her best friend, Delilah, has a costume emergency, the very fairy princess makes a sacrifice that lets her sparkle"--
Keywords: Costume -- Fiction; Halloween -- Fiction; Friendship -- Fiction; Schools -- Fiction; Princesses -- Fiction